2008
DOI: 10.1007/s00330-008-1196-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint involvement in juvenile idiopathic arthritis: clinical predictors of magnetic resonance imaging signs

Abstract: The aim of the study was to define clinical predictors of magnetic resonance imaging (MRI) findings of temporomandibular joint (TMJ) involvement in juvenile idiopathic arthritis (JIA). Forty-six patients, aged 2.08-36.7 years, with JIA (oligoartitular 18, polyarticular 17, systemic type 11) were examined with standard plain and contrast-enhanced sequences. Of 88 TMJs examined, an abnormal condyle was observed in 32%, flattened articular eminence in 27%, flattened articular disk in 17%, intra-articular fluid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
3
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 22 publications
6
41
3
10
Order By: Relevance
“…[18] For abnormal condyle and flattened articular eminence, independent predictors and risk factors for TMJ damage were a systemic type of JIA, young age at onset, and long disease duration. [31] In the present study, Sjögren's syndrome was shown in 25% of the cases. In another study, a higher frequency of TMJ and salivary gland dysfunction in RA patients was demonstrated, and disease activity (DAS28) was associated with both hyposalivation and TMJ pain and dysfunction.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…[18] For abnormal condyle and flattened articular eminence, independent predictors and risk factors for TMJ damage were a systemic type of JIA, young age at onset, and long disease duration. [31] In the present study, Sjögren's syndrome was shown in 25% of the cases. In another study, a higher frequency of TMJ and salivary gland dysfunction in RA patients was demonstrated, and disease activity (DAS28) was associated with both hyposalivation and TMJ pain and dysfunction.…”
Section: Resultsmentioning
confidence: 72%
“…[30] In another study, an abnormal condyle was observed in 32% of RA patients, flattened articular eminence in 27%, flattened articular disks in 17%, and restricted condylar motion in 9%. [31] In RA, clicking was the most frequent sign of TMJ involvement (48.8%). It was radiologically detected in 76.7% of patients, with synovial proliferation being the most frequent finding (51.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, most long-term studies, including those using MRI as a diagnostic method, will find rates of TMJ pathology of around 30-45% [5,9,31,32]: Stoll et al [31] found signs of acute or chronic TMJ arthritis after a mean disease duration of 2.5 years in contrast-enhanced MRI in only 43% of 185 patients and Argyropoulou et al [32] found abnormal condyles after a mean disease duration of 7.3 years in 32% of 46 JIA patients with TMJ MRI and enhanced pannus in 45%.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Twilt, et al 4 , only 12% of patients had TMJ pain; Billiau, et al found 22% with muscle or joint tenderness 5 , and Argyropoulou, et al found 5%−8% with pain or chewing discomfort 6 . Also, clinical examination is not able to reveal early signs of active TMJ arthritis, even when performed by skilled examiners; whether they are pediatric rheumatologists or orthodontists, they will reliably find only the signs of structural damage (growth delay, asymmetric movement on mouth opening), while early inflammation is missed 7 .…”
Section: The Difficult Diagnosis Of Temporomandibular Joint Arthritismentioning
confidence: 97%